Variations in the intensity of the securitization narratives at the EU level: securitizing the European refugee crisis - Stivas, Dionysios (Frontiers in Political Science, 2024)
This paper examines the narratives of the European Council, European Commission, and European Parliament regarding the European refugee crisis. Although the relevant scholarly research suggests that the EU Institutions held different perspectives about the refugee crisis, this paper argues that there was no such a clash of perspectives. This paper builds on the Copenhagen School’s securitization framework as complemented with subsequent methodological tools to support the author’s arguments. The findings suggest that despite the similarity in the views held by the main EU Institutions considering the refugees’ influx, there was a variation in the intensity of their securitizing narratives. Theoretically, this study develops an understanding of the importance of the securitization narratives’ intensity. Methodologically, this study introduces the Securitization Narratives Continuum, a research tool that facilitates the assessment of securitization. Empirically, this is the first study to interview and take into account the opinions of the securitizing actors.